When Uncertainty is the Only Constancy: The Agency and Serious Games of Sahrawi Men Migrating to Spanish Cities - Kluszczyńska, Marta (Lidé města, 2023)
This article aims to describe the situation of young Sahrawi migrants who live in Spanish cities and work in precarious conditions. To analyze and describe this phenomenon, I will use Sherry Ortner’s agency theory, focusing on the important aspects of values, social norms, and interdependent agency. The migration of Sahrawis from refugee camps in Tindouf (Algeria) is a consequence of the deteriorating humanitarian situation in the camps, diminishing international aid, and increasing inflation – a context in which migration to Europe is the best choice for supporting one’s family. Nonetheless, the situation for young Sahrawis in Spain is often one of precarious work, temporary legal status, and frequent changes of residence. Within systemic constraints, however, the strategies (e.g., career strategies) of Sahrawis can be understood as agency-as-project – in which crucial cultural values make it more important to support one’s family and loved ones living in the camps rather than to a mass financial capital. As a result, temporariness is the only constant characteristic of the life of this group of refugees, which is visible as a lack of long-term plans or opportunities related to migration.